Verticillium Ave1 effector induces tomato defense gene expression independent of Ve1 protein. (1st November 2016) - Castroverde, Christian Danve M.; Nazar, Ross N.; Robb, Jane
ABSTRACT: Verticillium resistance is thought to be mediated by Ve1 protein, which presumably follows a "gene-for-gene" relationship with the V. dahliae Ave1 effector. Because in planta analyses of Ave1 have relied so far on transient expression of the gene in tobacco, this study investigated gene function using stably expressing 35S: Ave1 transgenic tomato. Transgenic Ave1 expression was shown to induce various defense genes including those coding for PR-1 (P6), PR-2 (βbeta-1, 3-glucanase) and peroxidases (anionic peroxidase 2, Cevi16 peroxidase). Since a Ve1 − tomato cultivar served as germplasm, these results indicate that Ave1 induces these defense genes independently of Ve1.